Variation in health care spending : target decision making, not geography - Newhouse, Joseph P.; Garber, Alan M.; Graham, Robin P.; McCoy, Margaret A.; Mancher, Michelle; Kibria, Ashna (Online access: National Academy of Sciences National Academies Press., 2013)
"Variation in Health Care Spending investigates geographic variation in health care spending and quality for Medicare beneficiaries as well as other populations, and analyzes Medicare payment policies that could encourage high-value care. This report concludes that regional differences in Medicare and commercial health care spending and use are real and persist over time. Furthermore, there is much variation within geographic areas, no matter how broadly or narrowly these areas are defined. The report recommends against adoption of a geographically based value index for Medicare payments, because the majority of health care decisions are made at the provider or health care organization level, not by geographic units. Rather, to promote high value services from all providers, Medicare and Medicaid Services should continue to test payment reforms that offer incentives to providers to share clinical data, coordinate patient care, and assume some financial risk for the care of their patients."--Publisher's description.